2011
DOI: 10.1111/j.1528-1167.2011.03272.x
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive outcome after extratemporal epilepsy surgery in childhood

Abstract: SUMMARYPurpose: The present study aims to describe the cognitive profile of children with medically refractory extratemporal epilepsies who undergo focal surgery and to identify determinants for preoperative and postoperative cognitive level. Methods: This is a retrospective cohort study. Children who underwent operations between 1997 and 2008 with a focal lesion in frontal, parietal, or occipital cortices and with a presurgical or postsurgical cognitive evaluation, were eligible for the study. Key Findings: S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

5
49
1
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(57 citation statements)
references
References 28 publications
5
49
1
2
Order By: Relevance
“…In addition, the correlation between age and FSIQ in the pharmacoresistant group (n ϭ 28) was 0.35 ( p ϭ 0.06) which, in magnitude, is highly comparable to what others have reported in surgical series. [1][2][3][4][5] Finally, the associations between FSIQ 80Ͻ vs Ն80 and age at onset in those with and without pharmacoresistance were highly comparable to those in full group, with no evidence of a trend in the nonpharmacoresistant group ( p ϭ 0.61) and a striking trend ranging from 87% having FSIQ Յ80 for age Ͻ1 year to 0% for age 7 years ( p ϭ 0.001) (figure e-3).…”
Section: Resultsmentioning
confidence: 79%
See 1 more Smart Citation
“…In addition, the correlation between age and FSIQ in the pharmacoresistant group (n ϭ 28) was 0.35 ( p ϭ 0.06) which, in magnitude, is highly comparable to what others have reported in surgical series. [1][2][3][4][5] Finally, the associations between FSIQ 80Ͻ vs Ն80 and age at onset in those with and without pharmacoresistance were highly comparable to those in full group, with no evidence of a trend in the nonpharmacoresistant group ( p ϭ 0.61) and a striking trend ranging from 87% having FSIQ Յ80 for age Ͻ1 year to 0% for age 7 years ( p ϭ 0.001) (figure e-3).…”
Section: Resultsmentioning
confidence: 79%
“…There is an increasing body of literature demonstrating that, in children with refractory epilepsy who are evaluated for epilepsy surgery, earlier age at onset is associated with lower IQ or developmental scores, [1][2][3][4][5] and longer duration of epilepsy before surgery is negatively correlated with IQ and ability to rebound after surgery 2,4,6 . A drug treatment trial for infantile spasms reported a striking correlation between both age at onset and delay to treatment with developmental scores assessed later at age 4 years.…”
mentioning
confidence: 99%
“…19,23,33 However, literature evaluating cognitive outcome in young children to date has yielded contradictory and confusing results, perhaps stemming from methodological confounds. Outcome studies have yielded such varied results as 1) improved cognitive outcomes; 3,8,19,34 2) slight improvement in cognition being more likely than decline, with significant declines in some children; 37 3) reversible decline in at least some children, especially following left temporal lobectomy; 7 4) lack of improved outcome, with some cognitive recovery being a "bonus"; 28 5) "stabilized developmental velocity"; 6 6) no improvement in outcome postsurgery, 2,30 with this lack of improvement theorized to be associated with an abnormal neural substrate versus seizures per se; 30 and 7) no improvement, with the possibility of decline in some cases. 1 Although methodological issues are beginning to be addressed in adolescents and adults, 4 they have not been addressed to the same extent in children, particularly very young children.…”
mentioning
confidence: 99%
“…Generally, the pediatric surgical outcome literature has been muddied by heterogeneous samples, combining many factors, including 1) markedly different surgical therapies, from focal resections to hemispherectomies; 3,26,28 2) broad age inclusion criteria, at different developmental levels, from 6 to 17 or 18 years 30,37 or 1 to 15 years 1 or "all children"; 2 3) variable levels of functioning prior to resection; 30 4) wide ranges of presurgical seizure duration; 28 and 5) variable pathologies. 2,28 Because many pediatric studies have focused on different age ranges, some studies have attempted to narrow the developmental scope, but their methods have still varied from each other, making them difficult to compare. Age range samples include patients less than 6 or 7 years at surgery, 19,28 3 to 7 years, 6 8 to 159 months, 34 less than 3 years, 20,26 or 3 to 36 months.…”
mentioning
confidence: 99%
“…To date most studies investigating restingstate networks in patients with epilepsy have focused on adults with long-standing epilepsy. It is not known whether children with epilepsy also have impairment in the resting-state network and whether there is a relation between DMN and IQ, because reduced IQ is common in children with medically refractory epilepsy 16,17 and IQ provides a global measure of cognitive function. We hypothesized that ictal and/or interictal activity in children with medically refractory epilepsy leads to reduced functional connectivity within the DMN.…”
mentioning
confidence: 99%